2015
DOI: 10.5489/cuaj.3049
|View full text |Cite
|
Sign up to set email alerts
|

Urothelial bladder cancer in young adults: Diagnosis, treatment and clinical behaviour

Abstract: Introduction: The aim of the study is to reveal pathologic characteristics and clinical behaviour of patients 40 years old or younger diagnosed with and treated for urothelial bladder carcinoma. Methods: We retrospectively analyzed the clinical and pathologic data of 91 patients, initially diagnosed and treated at our institution from May 1996 to December 2014. Cancer recurrence was defined as new occurrence of bladder cancer at the same or different sites of the bladder. Cancer progression was defined as an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…20 Conflicting data regarding genetic factors, outcomes, and prognosis of early-onset urothelial cancer could be explained by the fact that there is no consensus on the definition of the cutoff threshold for "young patients"; some studies restrict analysis to patients younger than 20 years of age, other studies indicate the threshold of young age to be 25 or 30 years, while some authors include patients in this category up to 45 years of age. 17,[21][22][23][24][25][26] In our study, we analyzed patients younger than 45 years of age according to the World Health Organization standard age groups. We also stratified our cohort into subgroups by decades for statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…20 Conflicting data regarding genetic factors, outcomes, and prognosis of early-onset urothelial cancer could be explained by the fact that there is no consensus on the definition of the cutoff threshold for "young patients"; some studies restrict analysis to patients younger than 20 years of age, other studies indicate the threshold of young age to be 25 or 30 years, while some authors include patients in this category up to 45 years of age. 17,[21][22][23][24][25][26] In our study, we analyzed patients younger than 45 years of age according to the World Health Organization standard age groups. We also stratified our cohort into subgroups by decades for statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Urothelial carcinoma is a disease that typically affects the elderly (1-4). Bladder cancer constitutes a rare entity in patients younger than 40 years and even rarer in patients younger than 30 years (1, 3-6). The incidence of bladder cancer in patients younger than 40 years is reported to be 1-2.4%, while in patients younger than 20 is only 0.1-0.4% (1).…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis showed that patients with bladder malignancy aged ≤40-year-old often have a low-stage (63.2%) and low-grade (44.7%) tumor, which supports the previous evidence that patients at this age group had low stage and grade. [ 6 7 8 9 10 11 ] Tumor stage and grade is important in determining the natural history of the disease as well as the risk of recurrence. Compérat et al .…”
Section: Discussionmentioning
confidence: 99%